Regional interests in Europe : Wales and Saxony as modern regions - Mathias, Jörg (Frank Cass, 2004)
The question of how to organize and manage sustainable regional development has recently come to the fore in many places across the industrialized countries of Central and Western Europe, and especially within the European Union (EU). This book looks at the home-grown natural, economic and social, socio-political, political and administrative conditions which policy makers face, while also being subjected to numerous external influences. Political actors in less important EU regions attempt to create and implement strategies of regional development in the context of regional policy-maki.
Keywords: Regional planning -- Wales.; Regional planning -- Germany -- Saxony.; Regional planning -- European Union countries.; Aménagement du territoire -- Pays de Galles.; Aménagement du territoire -- Allemagne -- Saxe.; Aménagement du territoire -- Pays de l'Union européenne.; POLITICAL SCIENCE -- Public Policy -- Regional Planning.; Regional planning; European Union countries; Germany -- Saxony; Wales